PENINGKATAN PEMAHAMAN HUKUM PERDATA BAGI MASYARAKAT DALAM PENYELESAIAN SENGKETA SECARA DAMAI - Gunawan Widjaja (Lafadz Jaya Publisher, 2026)
This article discusses the importance of improving the public’s understanding of civil law in order to resolve disputes amicably. Civil law plays a central role in regulating legal relationships between individuals, particularly in matters of contracts, family, inheritance, property and other legal liabilities. The public’s limited understanding of civil law is often the cause of conflicts that could, in fact, have been prevented from the outset. Therefore, civil law literacy is a fundamental necessity to enable the public to properly understand their rights and obligations. Furthermore, the peaceful resolution of disputes through consultation, mediation, or other forms of alternative dispute resolution has proven to be more effective, efficient, and capable of maintaining good relations between the disputing parties. This study employs a literature review method, examining various relevant sources such as books, journals and legislation. The findings indicate that improving understanding of civil law can foster a more orderly, fair and harmonious legal culture within society.